Execution of Mortgage Objects in the Event of Non-Performing Loans Without Court Proceedings (Parate Executie) - Lasmini Lasmini; Geni Sapriani (CV WAHANA PUBLIKASI, 2026)
This article aims to analyze the material nature of mortgage rights, the position of the first mortgage holder as a preferred creditor, and the procedural limits of parate executie in non-performing loan cases. Using normative legal research, the study applies statutory, conceptual, case-based, and prescriptive approaches to Indonesian guarantee law, banking law, civil law, auction rules, and selected court-related materials. The study finds that a mortgage is not merely an accessory promise attached to a credit agreement, but a registered material security right that follows the object, is publicized through land registration, and grants priority to the preferred creditor. Parate executie is legally justified because Article 6 of the Mortgage Law authorizes the first mortgage holder to sell the mortgage object through public auction when the debtor defaults. However, this authority must be exercised through a rule-bound auction process supported by valid default, proper notification, transparent valuation, accurate documents, and access to legal remedies. The article concludes that parate executie should remain available as an efficient enforcement instrument, but it must not become arbitrary private dispossession.